A radiative transfer modeling approach for accurate interpretation of PAM fluorometry experiments in suspended algal cultures. (14th November 2016) - Murphy, Thomas E.; Prufert‐Bebout, Leslie E.; Bebout, Brad M.
Abstract : The results of a numerical study on the simulation of pulse amplitude modulated (PAM) fluorometry within dense suspensions of photosynthetic microorganisms are presented. The Monte Carlo method was used to solve the radiative transfer equation in an algae‐filled cuvette, taking into account absorption, anisotropic scattering, and fluorescence, as well as Fresnel reflections at interfaces. This method was used to simulate the transport of excitation and fluorescence light in a common laboratory fluorometer. In this fluorometer, detected fluorescence originates from a multitude of locations within the algal suspension, which can be exposed to very different fluence rates. The fluorescence‐weighted fluence rate is reported, which is the local fluence rate of actinic light, averaged over all locations from which detected fluorescence originated. A methodology is reported for recovering the fluorescence‐weighted fluence rate as a function of the transmittance of measuring light and actinic light through the sample, which are easily measured with common laboratory fluorometers. The fluorescence‐weighted fluence rate can in turn be used as a correction factor for recovering intrinsic physiological parameters, such as the functional cross section of Photosystem II, from apparent (experimental) values. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1601–1615, 2016